A Measure of an Individual's Power in a Group - Hofshi, Rami; Korsh, James F. (Management Science, 1972)
A mathematical model is presented for assigning numerical weights to each individual of an organization. The model is based on verbal definitions presently used in the social sciences to describe an individual's power or influence within a group of individuals. Thus the numerical weights derived can be interpreted as measures of the power or influence that individuals have in an organization. The model is not meant to be generally descriptive of group dynamics. It can be used, however, to obtain a group preference structure from individual preference structures.